Evaluation of Synthesized Catalytic Complex Structure-Forming Ability during Paraffin Base Tar Upgrade - F. Kemalov, Alim; A. Kemalov, Ruslan; Serge-Bertrand, Adiko (International Journal of Engineering and Technology, 2018)
The combination of the synthesized multicomponent bifunctional catalytic complex (MBC) components with heavy oil residues (HOR) of the paraffin-naphthenic (P-N) base leads to the chemical structuring of the hydrocarbon (HC) segments of the raw material molecules, and the specifics of HOR physicochemical structure, which will be the criteria for the selection of modifiers with a certain chemical nature [1,2,3,4]. It has been established that the introduction of catalytic activators in the tar composition promotes both the intensification of the oxidation process and the production of bituminous insulating material (BIM) with high physicomechanical properties [1,2,4].Raw materials for the production of special bituminous materials must be highly resinous with a P-HC content of up to 3% by weight. Based on the works by A.S. Kolbanovskaya [6], this is explained by the fact that the dispersed structure of bitumen is significantly dependent on the content of P-HC, since the dispersed phase in the oils is formed by naphthenic (N-) and PN-A-HC at certain temperatures with the side chains of the paraffinic P-HC series. If their content is more than 3% by weight the crystallization skeleton of P-HC is developed, which provides stiffness and reduces the plasticity interval for the system. Together with this, it is known that in the process of HOR oxidation the amount of low-molecular-weight oil A-HC decreases continuously, and the relative amount of PN-HC increases. Due to this, the affinity of the dispersion medium (DM) decreases to asphaltenes [7,8,9], which, moreover, becomes larger, which leads to THE deterioration of the cohesion and adhesion-strength properties of BIM.Â Â